Comparative Characteristics of the Constitutional and Legal Status of the Senior Official of the Constituent Entities of the Russian Federation – the Cities of Moscow and St. Petersburg - M. A. Volochkovskaya (Теоретическая и прикладная юриспруденция)
The article provides a theoretical and comparative analysis of the constitutional and legal status of the senior official of the constituent entities of the Russian Federation — the cities of Moscow and St. Petersburg. The author highlighted the main elements of the constitutional and legal status of a senior official of a constituent entity of the Russian Federation, the classification of which became the basis for the proposed methodology for a comparative analysis of the statuses of senior officials of cities of federal significance (Moscow and St. Petersburg) in the context of regional norms.A comparative analysis based on the proposed methodology led to conclusions about the similarities and differences in the constitutional and legal statuses of the Moscow Mayor and the Governor of St. Petersburg.